Anti-streptococcus mutans, anti-adherence and anti-acidogenic activity of uvaria chamae P. beauv (2023)
Ethnopharmacological relevance. Streptococcus mutans a key pathogen, produces biofilm, acids and extracellular polysaccharides in the oral cavity; which leads to the development of dental caries. Control of these pathogenic markers can prevent dental caries. Uvaria chamae P. Beauv. is a medicinal plant traditionally used for many ailments including oral infections. Root, leaves and bark extracts has proven antibacterial activity including activity against caries causing S. mutans. However, its effect on the virulence properties of S. mutans, responsible for the development of dental caries, has not been studied. Aim of the study This study investigated the phytochemical constituents, anti-S. mutans, anti-adherence and antiacidogenic activity of U. chamae root extract. Materials and methods Extracts were prepared and phytochemical analysis was performed. Minimum inhibitory concentrations (MIC) were determined, and MIC and sub-MIC concentrations of the best solvent were selected for their effect on the virulence factors of S. mutans. The results were analysed using one-way ANOVA and Wilcoxon Rank Sum Tests. Results The ichloromethane extract, with proanthocyanidin as a major chemical constituent, produced an MIC of 0.02 mg/ml. At 6 h, exposure to 0.005, 0.01, and 0.02 mg/ml extract significantly reduced S. mutans adherence by 39, 59, and 77% respectively (p < 0.05). Uvaria chamae also significantly inhibited acid production in S. mutans at 10, 12, 14 and 16 h (p < 0.05). At ½ MIC, the plant extract caused remarkable downregulation of the virulence genes responsible for the adherence, biofilm formation, extracellular polysaccharide synthesis and acid production. Conclusions This suggests that U. chamae extract may potentially be used to inhibit the proliferation of S. mutans and silencing the expression of pathology-related genes, which will prevent the development of dental caries.